Динамика деформации объекта при магнитно-импульсной обработке материала с учетом пластических деформаций и температуры нагрева заготовки - Байда, Евгений Иванович (НТУ "ХПИ", 2011)
В статье рассмотрена динамика деформации цилиндрической трубки при воздействии на нее магнитного поля с учетом пластичности материала и температуры воздействия.

In the article, the dynamics of cylindrical tube deformation is considered under magnetic field action taking into account plastic strain and heating temperature of the workpiece.
Object deformation dynamics under magnetic-pulse treatment of material with allowance for the workpiece plastic strain and heating temperature
Keywords: цилиндрическая трубка; вихревые токи; разряд; накопители энергии; magnetic-pulse treatment; electromagnetic force; deformation; pressure